Peningkatan Nilai Kekerasan Baja Karbon Rendah AISI 1018 melalui Proses Pack Karburizing dengan Media Batok Kelapa - Imam Prabowo; Abdu Halim Wibowo; Fajar Paundra; Eko Pujiyulianto; Muhammad Ichsanudin (Journal of Metallurgical Engineering and Processing Technology, 2023)
Low carbon materials are one of the steels which have a composition of carbon ranging from 0.005 to 0.3%. Generally, these materials have good ductility and flexibility so they are good enough to be applied for automotive industry’s components. Unfortunately, they do not possess an excellent hardness as well as wear resistance. Thus, in order to enhance the hardness and wear resistance, carburizing is obligatory required. The carburizing process is a diffusion of carbon from the higher to lower concentration in a high temperature condition, following the gradient concentration. In addition, the process demands a source of active carbons and energizer. In this study, the coconut shells are possibly harnessed as a high-rich carbon material besides charcoals due to its availability and environmentally-friendly materials. Hardness test is measured in ten distinct points by using vicker-hardness scale in accordance with ASTM E 384. The hardness of the AISI 1018 increases after pack carburizing process by nearly 20 HVN. It grows from 131 HVN before the process to 150 and 165 HVN after the heating by 900°C and 950°C respectively. The increase is affected by the diffusion of carbon from coconut shells into the layer of AISI 1018 in which the coconut shells are having a higher carbon content compared to the layer. Furthermore, the higher heating temperature will accelerate the diffusion rate of carbon. As a result, the hardness of AISI 1018 at the higher heating temperature will also become larger.